Probiotic effect and dietary correlations on faecal microbiota profiles in irritable bowel syndrome. Issue 3 (3rd July 2021) - Stevenson, Cheryl; Blaauw, Renée; Fredericks, Ernst; Visser, Janicke; Roux, Saartjie
Abstract : Objective: Probiotics and nutrient intakes modulate gastrointestinal (GIT) microbiota and symptoms of irritable bowel syndrome (IBS). The extent to which these factors influence the microbiota is relatively unknown. The primary objective of this paper was to investigate the effect of a probiotic on gut microbiota and IBS symptoms. The secondary objective was exploring correlations between dietary intake and gut microbiota. Design: This study was an extension of a randomised clinical trial (Clinical Trials Registry NCT018867810). Dietary intake was recorded by three-day estimated food records. Faecal samples were collected at three time points: (1) baseline (A), (2) after eight weeks' probiotic supplementation ( Lactobacillus plantarum 299v) (B) and (3) following a two-week washout period (C). Total Bacteroides spp., Bifidobacteria bifidum and Lactobacillus plantarum were quantified by quantitative real-time polymerase chain reaction (qPCR). Results: Twenty-eight diarrhoea-predominant IBS (D-IBS) and 24 constipation-predominant IBS (C-IBS) patients participated. Lactobacillus plantarum profiles at baseline (A) were significantly different between C-IBS and D-IBS (−0.956 ± 1.239 vs. −1.700 ± 1.239; p = 0.024). There was no significant change in bacterial counts after completion of the trial (B) and following the washout period (C) between groups. In both groups there were significant direct correlations between fibre and Lactobacillus plantarum and inverse correlations between fibre and Bacteroides spp. There was no difference in symptom severity scores between treatment and placebo groups during the study. Conclusion: The probiotic had no effect on symptoms and GIT microbiota. Certain nutrients strongly correlate to certain bacterial profiles, suggesting that nutrients can significantly influence gastrointestinal microbiota composition.